Peran Perawat dan Management Infeksi Dengan Mengontrol Penggunaan Antibiotik - Elin Hidayat; Sri Marnianti Irnawan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background: Infection is a big problem that is often faced by patients. This can be caused by antibiotics that are not suitable, even due to resistance from the use of antibiotics. Method: in searching for literature for this review using articles in English originating from Scopus, Science Direct, and Proquest from 2017 to 2020 and in compiling results related to articles using the appropriate rules, namely using Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) as well as flow charts. Result: An initial search from Science Direct, Scopus and Proquest data yielded a total of 1,340 literature articles. Articles are then excluded based on changes in sources, namely the last 5 years from 2018 to 2023 with the method of systematic review and original articles from research. Recently found 10 articles ready to be synthetic. Conclusion: Complications due to less optimal use of antibiotics often occur, such as prolonged infection and resistance to anaphylaxis. Many programs are implemented in the management of controlling the administration of antibiotics, this aims to avoid prolonged infection and resistance to these drugs.